2018
DOI: 10.1007/s40618-018-0889-x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between obesity and aggressiveness of differentiated thyroid cancer

Abstract: Obesity was not associated with aggressive features in this prospective, European cohort of patients with DTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 33 publications
1
32
5
Order By: Relevance
“…Another factor that should be taken into account when considering the role of obesity in thyroid cancer is the potential for a delay in diagnosis due to difficulties in detecting thyroid nodules during neck examinations of obese patients. Although the present study and others did not find increased BMI to be associated with larger tumor [ 26 , 51 , 52 ], other studies have observed this trend [ 47 , 48 , 55 ]. Additionally, Tresallet et al reported that obese patients with PTC >10 mm had an increased risk of persistent / recurrent disease (OR = 3.8, 95% CI: 1.6–8.8; p = 0.03)[ 55 ].…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Another factor that should be taken into account when considering the role of obesity in thyroid cancer is the potential for a delay in diagnosis due to difficulties in detecting thyroid nodules during neck examinations of obese patients. Although the present study and others did not find increased BMI to be associated with larger tumor [ 26 , 51 , 52 ], other studies have observed this trend [ 47 , 48 , 55 ]. Additionally, Tresallet et al reported that obese patients with PTC >10 mm had an increased risk of persistent / recurrent disease (OR = 3.8, 95% CI: 1.6–8.8; p = 0.03)[ 55 ].…”
Section: Discussioncontrasting
confidence: 89%
“…In the current study of patients with DTC, there was no relationship between BMI and aggressive clinicopathological features, the degree of clinical progression, the response to primary treatment, or the outcome of the disease. In addition, BMI was not a significant predictor of high or intermediate risk of recurrence according to the ATA Risk Stratification system, as reported by Grani et al [ 52 ]. Our results are in line with those of Kwon et al [ 51 ], in which the authors did not find any association between BMI and clinicopathological features of thyroid cancer or disease outcome.…”
Section: Discussionsupporting
confidence: 57%
“…Obesity was positively related to papillary, follicular and anaplastic thyroid cancers, but negatively with medullary thyroid cancer (75). The impact of obesity on thyroid cancer aggressiveness has still to be defined (76). Importantly, data showing that early detection of thyroid cancer by systematic ultrasound assessment improve the prognosis of thyroid cancer in patients with obesity are lacking.…”
Section: Reasoningmentioning
confidence: 99%
“…Similarly, a strong U-shaped association exists between iodine intake and the frequency of diffuse goiter, with low and high iodine intakes associated with increased rates of thyroid disease; nevertheless, the risk of nodular goiter is perhaps increased only at low intakes 424344Table 1. details other risk factors 1835384546474849505152535455565758596061…”
Section: Risk Factors For Thyroid Nodules and Thyroid Malignancymentioning
confidence: 99%